Formulation of water-soluble Buddleja globosa Hope extracts and characterization of their antimicrobial properties against Pseudomonas aeruginosa - Araya, Nicolas; Leiva-Soto, Martín A.; Bruna, Maria V.; Castro-Munoz, Almendra; Behrend-Keim, Beatriz; Moraga-Espinoza, Daniel; Bahamondez-Canas, Tania F. (Frontiers in Pharmacology, 2022)
Buddleja globosa Hope (BG) extracts are traditionally used to treat skin and gastric ulcers due to their healing properties. Non-aqueous solvents such as ethanol and DMSO are usually used to extract naturally occurring compounds. However, the cytotoxicity of these solvents and the low water solubility of the extracted compounds can hinder their biomedical applications. To overcome the limited solubility of the BG extracts, we aimed to enhance the solubility by processing a standardized hydroalcoholic extract (BG-126) through spray drying (SD), with and without two solubility enhancers. Spray-dried BG (BG-SD) extracts and spray-dried BG extracts plus polyvinylpyrrolidone (BG-SD PVP) and Soluplus® (BG-SD SP) were developed starting from BG-126 (containing 53% ethanol). These four formulations were characterized by total phenolic content, water solubility at 25°C and 37°C, and antimicrobial properties against Pseudomonas aeruginosa. All the SD formulations presented a solubility that allowed them to reach maximum concentrations of 1,024 μg/ml catechin for BG-SD and 2,048 μg/ml catechin for BG-SD PVP and BG-SD SP for antimicrobial testing. BG-SD showed the highest antimicrobial potency with a minimum inhibitory concentration (MIC) of 512 μg/ml catechin, followed by BG-126 with a MIC of 1,024 μg/ml catechin and SP. BG-126 was also shown to inhibit biofilm formation, as well as the excipients PVP and SP. The spray-dried BG (BG-SD) extract represents a promising natural active component with enhanced antimicrobial properties against P. aeruginosa for further research and the development of novel phytopharmaceuticals.